A course and a didactic model library on automation of energy systems. Issue 17 (2022) - Leva, Alberto
Abstract: The paper presents a course on automation of energy systems, and a companion model library. Peculiar to the proposed didactic activity is to concentrate on the control layer that provides the individual units in the system with the capability of integrating into higher-level optimisation frameworks (a subject that probably deserves more attention than it generally receives). Also, the activity explicitly focuses on inducing a system-level view on the addressed control problems. The course thus provides a trait d'union between detailed teaching about individual components such as electric machines on one side, and methodologically oriented courses about wide-scale optimisation on the other.